2016
DOI: 10.1186/s12866-016-0655-1
|View full text |Cite
|
Sign up to set email alerts
|

The ATP-dependent RNA helicase HrpB plays an important role in motility and biofilm formation in Xanthomonas citri subsp. citri

Abstract: BackgroundRNA helicases are enzymes that catalyze the separation of double-stranded RNA (dsRNA) using the free energy of ATP binding and hydrolysis. DEAD/DEAH families participate in many different aspects of RNA metabolism, including RNA synthesis, RNA folding, RNA-RNA interactions, RNA localization and RNA degradation. Several important bacterial DEAD/DEAH-box RNA helicases have been extensively studied. In this study, we characterize the ATP-dependent RNA helicase encoded by the hrpB (XAC0293) gene using de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 52 publications
2
35
1
Order By: Relevance
“…The most specifically highly upregulated gene in our analysis was Varpa_1640 (Table 1, green ), which was not identified in our previous biofilm mutant screen. This protein is predicted to be a DEAD-box RNA helicase, a widespread family of proteins recently shown to play a role in biofilm formation [26]. We hypothesize that this protein is active in RNA turnover in V. paradoxus EPS based on the KEGG predicted RNA degradation pathway [27] (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most specifically highly upregulated gene in our analysis was Varpa_1640 (Table 1, green ), which was not identified in our previous biofilm mutant screen. This protein is predicted to be a DEAD-box RNA helicase, a widespread family of proteins recently shown to play a role in biofilm formation [26]. We hypothesize that this protein is active in RNA turnover in V. paradoxus EPS based on the KEGG predicted RNA degradation pathway [27] (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The PNPase, enolase, and RNAses are all highly expressed in biofilm ( Supplemental Data S1, S2 ), leading to the hypothesis that differential expression of Varpa_1640 is a mechanism for regulating RNA stability and drastically altering the gene expression profile. A relationship between a DEAD-box helicase and biofilm growth was recently described in the plant pathogen Xanthomonas citri [26], based on mutations in the HrpB helicase resulting in reduced expression of Type IV pili. Intriguingly, our prior work indicated that Type IV pili are critical for the switch between biofilm and swarming phenotypes in V. paradoxus EPS [15], suggesting a possible link between RNA stability, pilus formation, and attachment phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Motility assays were performed as previously described (40). Bacteria were grown overnight in NBY medium, and 3 µL of bacterial culture (OD600 0.3) was then spotted onto a plate containing SB medium plus 0.5 % (wt/v) agar (Difco, Franklin Lakes, NJ) (41) for the sliding motility tests or NYGB medium 0.25 % (wt/v) agar (42) for the swimming motility tests.…”
Section: Methodsmentioning
confidence: 99%
“…The most specifically highly upregulated gene in our analysis was Varpa_1640 (Table 1, green), which was not identified in our previous biofilm mutant screen. This protein is predicted to be a DEAD-box RNA helicase, a widespread family of proteins recently shown to play a role in biofilm formation [33]. We hypothesize that this protein is active in RNA turnover in V. paradoxus EPS based on the KEGG predicted RNA degradation pathway [34] (Fig.…”
Section: Rna Turnover Role In Biofilm Regulationmentioning
confidence: 97%
“…The PNPase, enolase and RNAses are all highly expressed in biofilm (Supplementary Data S1 and S2), leading to the hypothesis that differential expression of Varpa_1640 is a mechanism for regulating RNA stability and drastically altering the gene expression profile. A relationship between a DEAD-box helicase and biofilm growth was recently described in the plant pathogen Xanthomonas citri [33], based on mutations in the HrpB helicase resulting in reduced expression of type-IV pili. Intriguingly, our prior work indicated that type-IV pili are critical for the switch between biofilm and swarming phenotypes in V. paradoxus EPS [22], suggesting a possible link between RNA stability, pilus formation and attachment phenotypes.…”
Section: Rna Turnover Role In Biofilm Regulationmentioning
confidence: 99%